WATER QUALITY ASSESSMENT AND POLICY EVALUATION OF LAKE DANAO, PHILIPPINES - Abejo, Maximino R (Journal of Agriculture and Technology Management, 2022)
The current condition of Lake Danao in San Francisco, Cebu, Philippines, specifically on water quality, policies, and community participation as bases for lake management is the focus of this study. Basic parameters to test the water quality were examined on- site. Some parameters were tested in the water laboratory for analysis. Policies were obtained from the records of the Local Government Unit (LGU) of the municipality of San Francisco about the utilization of Lake Danao. Municipal ordinances were present and available intended for the conservation of the lake. Community participation was also assessed and evaluated. Moreover, the GERMADAN framework was utilized in this study for successful lake management. Results showed good lake water quality except for total phosphorus, which indicates nutrient leaching from fertilizers and animal manure within the periphery of Lake Danao. Policies were existing but needed thorough monitoring for proper implementation. People's organizations for lake conservation emerged but not that stable and active to pursue the organization's objectives. To appropriately manage the lake, based on results, recommendations such as the making of policies prohibiting the use of chemical fertilizers and other agricultural activities which may degrade the quality of the lake, strengthening the existing policies through conducting seminars to develop an awareness of the people and to encourage the public to participate in the conservation and management of the lake for its betterment should be implemented faithfully.